Local Wisdom of Desa Gadang Village of Kampar Regency In An Effort To Improve Tourism Potency of Riau Province - Geovani Meiwanda (Indonesian Association for Public Administration (IAPA), 2018)
The village of Pulau Gadang District XII Koto Kampar, Kampar regency is a village that has an interesting historical value. Starting from the transfer of old Gadang Island Village to the current area due to the Koto Panjang PLTA Project, drowning four villages including Pulau Gadang Village. After 25 years passed the transfer was successful to give a positive impact, although initially received rejection. Improving the economy of local communities, supported by the tourism potential that recently developed in the area of this village and directly managed by the community of Pulau Gadang Village. Tourist attraction that is currently viral enough that Raja Ampat his Riau, at the beginning of the emergence of a very loved but the highest point of achievement only up there only. Tourism sector is a leading sector that is being developed and managed directly by the surrounding community, of course the positive impact of increasing the tourism potential in Riau. this paper will provide an in-depth analysis of the local wisdom of the community of Pulau Gadang Village that manages tourism directly, based on the construction of the concept of local wisdom that is capable of bringing progress to a region. Local wisdom is now an interesting issue as it returns to the foundation of a development theory that post modernism that can succeed a region is when the specialty of the area can be managed properly. Local wisdom that has influence in attitude and action, local local ideas that are wise, full of wisdom, good value, embedded and followed by members of the community.